ANALISIS KEPASTIAN HUKUM TERHADAP HAK EKSEKUTORIAL OBJEK JAMINAN FIDUSIA YANG DIMILIKI KREDITUR PADA PASAL 15 UNDANG-UNDANG NOMOR 42 TAHUN 1999 TENTANG JAMINAN FIDUSIA SETELAH PUTUSAN MAHKAMAH KONSTITUSI NOMOR 18/PUU-XVII/2019 - Angga Pratama; Endang Pandamdari (Jurnal Hukum Adigama, 2020)
The transfer of an ownership right based on trust is a Fiduciary Guarantee, so that the possession of the collateral object rests with the object owner. As a result of the possession of the object is at the Fiduciary Giver, often when the Fiduciary Recipient will exercise the executorial rights, sometimes the Fiduciary Guarantee object has been lost or damaged or changed hands, resulting in damage or decline in the value of Fiduciary Security goods because it is not maintained by the debtor, causing losses to creditors. However, there is a Constitutional Court Decision which does not necessarily have an executive power in the Fiduciary Guarantee certificate, and an agreement between the parties is required or legal action is taken in determining the breach of promise. Causing questionable legal issues, namely:How is the legal certainty of the creditor to the strength of the executive right contained in Article 15 of the Fiduciary Guarantee Law after the Constitutional Court Decision Number 18 / PUU-XVII / 2019. Based on the formulation of the problem, the normative juridical method is used. Based on the results of the study, it was found that Article 15 of the Fiduciary Guarantee Law was declared unconstitutionality by the Constitutional Court, and showed no legal certainty for creditors. This results in the removal of an easy mechanism that will make it attractive for creditors. The results of this study are useful for the Government of Indonesia in the future, so they can be more comprehensive.